Resolution of the board of directors of the authority No. 172/2014 dated 21/12/2104 concerning the conditions, rules, and procedures of licensing the companies to practice the activity of microfinance - The Egyptian financial supervisory authority (2025)
Egyptian Financial Supervisory Authority resolution of the board of directors of the Authority no. 172 of the year 2014 dated 21/12/2014 concerning the conditions, rules and procedures of licensing the companies to practice the activity of microfinance الهيئة العامة للرقابة المالية قرار مجلس إدارة الهيئة رقم 172 لسنة 2014 بتاريخ 21/12/2014 بشأن شروط وقواعد وإجراءات الترخيص للشركات بمزاولة نشاط التمويل متناهى الصغر